Complementary and Alternative Medicine Use by Patients From the Gulf Region Seen in the International Practice of a Tertiary Care Medical Center - Esayas B Kebede MD; Judy Tan MD; Salma Iftikhar MD, MS; Haitham S. Abu Lebdeh MD; Murali K Duggirala MD; Amit K Ghosh MD; Ivana T Croghan PhD; Sarah M Jenkins MS; Saswati Mahapatra MS; Brent A Bauer MD; Dietlind L Wahner-Roedler MD (SAGE Publishing, 2021)
Background Patients from various countries may have unique patterns of using complementary and alternative medicine (CAM) and unique reasons for using it. Objective Our objective was to assess the use of CAM among patients from the Gulf region attending the Executive and International Health Program of the Department of General Internal Medicine at Mayo Clinic in Rochester, Minnesota. Methods This cross-sectional survey was administered to all patients who were from the Gulf region and were undergoing outpatient evaluation in the Executive and International Health Program. After their initial medical evaluation by a physician, the patients were invited to anonymously complete the modified International Complementary and Alternative Medicine Questionnaire. Results The survey was completed by 69 patients (41 women, 27 men; mean age, 45.4 years). The most frequently seen providers for CAM treatments were physicians (71.0% of patients), spiritual healers (29.0%), and chiropractors (20.3%). CAM treatments most frequently received from a physician were massage therapy (51.0%), hijama (38.8%), spiritual healing (24.5%), and acupuncture or herbs (16.3%). The most frequently used dietary supplements were ginger (42.0%), bee products (30.4%), and garlic (27.5%). The most common self-help therapies were prayers for health (68.1%), meditation (15.9%), and relaxation techniques (11.6%). CAM therapy, including visits to CAM providers, was used by 92.8% of patients. CAM was mainly used to improve well-being and long-term health conditions rather than for acute illnesses. Conclusion The use of CAM was high among our patients from the Gulf region, and the CAM therapies used by this population differed from the ones used by US patients. Physicians providing care to patients from the Gulf region should be aware of how the use of CAM may affect the care needs of these patients.